A colaboração intérprete-compositor na elaboração da obra “Uma Lágrima” de Arthur Rinaldi - Morais, Augusto Alves de (2013)
This research presents a detailed report of the process of collaboration experienced by the author of this work with the composer Arthur Rinaldi during the creation of "Uma Lágrima" for solo vibraphone, demonstrating how the participation of the interpreter can be active and contributory. During this process, the author of this text contributed in various stages of the creation, from the commission, conception, composition and notation, to the premiere performance and recording of the piece. This text contains information about the development of this solo piece for vibraphone and about its sonorities, as well as issues of technical and interpretive nature which helped mold its final form, information collected during encounters with the composer during the year of 2011.